Barakah Beats - Siddiqui, Maleeha (Scholastic Press, 2021)
"It's Nimra Sharif's first time going to public school. Nimra's nervous, but as long as she has her best friend, Jenna, by her side, she figures she can take on just about anything. Unfortunately, middle school is hard. The teachers are mean, the schedule is confusing, and Jenna starts giving hijab-wearing Nimra the cold shoulder aorund the other kids. Desperate to fit in and save her friendship with Jenna, Nimra accepts an unlikely invitation to join Barakah Beats, a band made up of popular eighth-grade boys. The only problem is, Nimra was taught that music isn't allowed in Islam, and she knows her parents would be disappointed in her. So she devises a plan: join the band just until she wins Jenna back, then quit before her parents find out. but Nimra's lies quickly start to unravel. And as she grows to care about her bandmates, Nimra has to decide whether to betray her new friends or herself"--Provided by publisher.